Makna Menjadi Aktivis Gerakan Hak-Hak Disabilitas Di Bali: Studi Fenomenologis Tentang Pengalaman Aktivis Gerakan Sosial - I Made Anom Wiranata (Badan Strategi Kebijakan Hukum, 2023)
The disability rights movement is exercised by movement actors who are able to transform their experiences of suffering into power to bring about changes toward the fulfillment of the rights of persons with disabilities. This research discusses the relationship between the reconstruction of past experiences of grievances due to stigma and discrimination, collective identity, and the capacity to be involved in the disability rights movement. By taking a location in Bali, this research uses a qualitative-phenomenology methodology to reveal the meaning of the experiences of the subjects who are disability rights movement activists, in the process of involving themselves in social movements. This article finds that the social movement actors are able to reconstruct their suffering into the capacity to make changes. Their personal identity meets their collective identity as actors in the disability rights movement through interaction with the community which provides space for the emergence of new awareness about rights and advocacy strategies. The UNCRPD ratification, socialized by civil society organizations, opened up opportunities for strengthening interactions and networks between disability rights activists at the national and local levels. This network has strengthened the confidence of activists in Bali to take collective action. The ratification of the UNCRPD is also a momentum for mobilizing movement resources to change the old frame of charity towards a new frame of the fulfilment of rights. Changing the framework was carried out by advocating Regional Regulations in Bali which are in line with the spirit of the UNCRPD. Besides that, activists through their daily activities, show the public that persons with disabilities can be independent and actualize their potential if they get the chance.